Clonal expansion and diversification of germinal center and memory B cell responses to booster immunization in primates - Lachlan P. Deimel; Yoshiaki Nishimura; Gabriela S. Silva Santos; Viren A. Baharani; Brianna Hernandez; Thiago Y. Oliveira; Andrew J. MacLean; Marie Canis; Sadman Shawraz; Anna Gazumyan; Harald Hartweger; Paul D. Bieniasz; et al. (Cell Reports)
Summary: Effective vaccines elicit B cell clonal expansion in germinal centers (GCs) that produce memory B cells and antibody-secreting plasma cells. In mice, memory B cells rarely re-enter GCs upon boosting and instead differentiate into plasma cells. However, mouse circulating memory constitutes only 1%–2% of B cells, compared to 30%–50% in primates. We examine memory and GC B cell responses in rhesus macaques immunized and boosted ipsilaterally or contralaterally with an mRNA vaccine encoding the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein. The neutralizing activity of antibodies cloned from the memory compartment, as well as the size of the compartment, was independent of the site of boosting. We show that memory B cells enter and undergo iterative expansion in newly developing GCs when boosting is at a site distal to the site of priming. Thus, in primates, high-affinity memory B cells constitute a reservoir that actively participates in further development of immunity irrespective of the anatomical site of vaccine boosting.